Optimization of disinfection by-product analysis methods for IMO G9 approval. (January 2018) - Lee, Jihyun; Sim, Wonjin; Im, Youngkeun; Hwang, Euntae; Heo, Jinju
Abstract: This study assessed the methods for analyzing disinfection by-products (DBPs) to determine which were most suitable for ballast water in an approval test according to the Procedure for Approval of Ballast Water Management Systems that make use of Active Substances (G9). The existing analysis methods are optimized for drinking water. Therefore, it is necessary to assess the characteristics of ballast water, which has high levels of total residual oxidants (TROs) and salinity, prior to applying the existing methods. Sample preservation, pre-treatment and instrumental analysis methods were summarized based on certified test methods and the G9 final approval reports. Following the assessment, applicable methods were selected in consideration of the matrix effect arising from the high levels of TROs and salinity. The applicability was assessed using seawater and brackish water. The results are expected to be applied to the G9 test as well as in investigations of DBPs in ballast water. Graphical abstract: Highlights: This study assessed analytical methods for disinfection by-products for G9 approval. Sample preservation was improved to remove a high level of total residual oxidant. Optimum analytical methods were finalized through a matrix effect assessment.